Wildlife Tourism at Chitwan National Park: Evaluating the Perception of Tourists About Jeep Safaris - Aryal, Chandra Mani (International Journal of Environment, 2023)
This study was designed to collect tourist perceptions on aspects of Jeep safaris. A standard checklist containing questions related to the general background of the respondents, their experience with jeep safari at Chitwan National Park (CNP), and their perception of the impact of jeep safari on aspects of wildlife were prepared. Furthermore, tourism stakeholders bring up the discussion of night safaris at CNP as a product diversification option. Thus, the question related to the night safari was also included in the questionnaire. The responses of the visitors were collected using an online survey. The data was analyzed using Microsoft Excel and JASP software. Beeshazari and Kumroj were found to be more common than the core area for wildlife safaris. The respondent perceived that the wildlife was negatively impacted by Jeep Safari, and the overall management of Jeep Safari was satisfactory in all three locations. Majority of respondents believed that nature guides have moderate to extensive experience. More than half of the respondents were satisfied with their Jeep safari experience. Almost three-quarters of respondents expressed their opposition to the decision to launch a night safari at CNP. A statistically significant relationship was observed between the perception of the tourist about the impact on wildlife and their decision about a night safari. Controlling Jeep Crowd was the top suggestion received from the respondents. These findings can help management authority to amend the operation of the Jeep Safari at CNP so as to enhance visitor satisfaction and ensure the sustainability of the operation.